2016
DOI: 10.1126/science.aaf1525
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneously dispersed multimetal oxygen-evolving catalysts

Abstract: Earth-abundant first-row (3d) transition metal-based catalysts have been developed for the oxygen-evolution reaction (OER); however, they operate at overpotentials substantially above thermodynamic requirements. Density functional theory suggested that non-3d high-valency metals such as tungsten can modulate 3d metal oxides, providing near-optimal adsorption energies for OER intermediates. We developed a room-temperature synthesis to produce gelled oxyhydroxides materials with an atomically homogeneous metal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
1,515
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,109 publications
(1,611 citation statements)
references
References 55 publications
43
1,515
2
1
Order By: Relevance
“…Among the oxides composed of earth‐abundant materials, nickel–iron (oxy)hydroxide has been recently reconfirmed as a promising electrode in alkaline media 135, 136, 137, 138. In 2016, superior OER performance was revealed for the Ni–Co–W mixed oxyhydroxide, which requires an overpotential of only 191 mV to reach 10 mA cm −2 in 1.0 mol L −1 NaOH,139 and for Au‐supported NiCeO x , which reaches 10 mA cm −2 at an overpotential of 271 mV in 1.0 mol L −1 NaOH 140…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 99%
“…Among the oxides composed of earth‐abundant materials, nickel–iron (oxy)hydroxide has been recently reconfirmed as a promising electrode in alkaline media 135, 136, 137, 138. In 2016, superior OER performance was revealed for the Ni–Co–W mixed oxyhydroxide, which requires an overpotential of only 191 mV to reach 10 mA cm −2 in 1.0 mol L −1 NaOH,139 and for Au‐supported NiCeO x , which reaches 10 mA cm −2 at an overpotential of 271 mV in 1.0 mol L −1 NaOH 140…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 99%
“…However, the catalytic efficiency is still far from ideal and one of the significant factors that limit the practical utilization is the sluggish reaction kinetics of oxygen evolution half‐reaction 71, 72. Studies found that coupling effect between ultrathin structure construction and multinary component tuning can create outstanding OER performance 73.…”
Section: Energy Catalytic Applicationsmentioning
confidence: 99%
“…For example, in the field of clean technology, soft (SGM) and hard X-ray techniques (HXMA) can bring new insight to important modern energy questions including the production of hydrogen from water splitting for fuel cell operations by better understanding more efficient catalysts that can be produced from abundant low-cost metals [10].…”
Section: Phase-i Experimental Facilitiesmentioning
confidence: 99%